Bilateral biomechanical asymmetry during 30 seconds isokinetic sprint-cycling exercise - Rannama I.; Port K. (LASE Journal of Sport Science, 2015)
The purpose of present study was to examine the bilateral differences of pedalling kinetics and thigh muscle activity patterns according to leg dominance during the 30 seconds maximal cycling exercise and to analyse the relationships between asymmetries of pedalling kinetics and muscle activity. Methods: The pedalling power (POW), power production smoothness (PS) and EMG of VL, RF and BF of 17 competitive cyclists (19.2±1.6y.; 1.82±0.07m; 74.1±8.2kg) were measured bilaterally during maximal 30s isokinetic (cadence limit 100 rpm) seated cycling exercise. The dynamics of POW, PS and normalized EMG-RMS amplitude and median frequency (MF) of dominant (DO) and non-dominant (ND) side were measured. The directional asymmetry indexes (AI%) between DO and ND side were computed and compared with student t-test for paired samples. Correlation analyse between AI(%) of pedalling kinetics and EMG patterns was made. Results: The DO side POW and PS values were significantly (p<0.05) higher than ND during the all exercise time (except POW between 5-10 sec). No significant bilateral differences were found between normalized EMG amplitude values. The AI(%) of POW and PS were significantly lowered during the exercise. Significant correlations were found between AI (%)-s of PS and VL EMG MFr (r=-0.64) and between AI(%)-s of POW and VL normalized EMG amplitude (r=0.63).Conclusions: Results of the present study indicate that during 30 seconds maximal intensity cycling does exist leg dominance dependent asymmetries in pedalling power patterns, which decreased during the exercise and was related with bilaterally asymmetry of vastus lateralis muscle firing patterns.